Chemo-enzymatic synthesis of (R)-5-hydroxymethyl-2-isopropyl-5-methylcyclopent-1-en-1-yl trifluoromethylsulfonate, a potential chiral building block for multicyclic terpenoids. Issue 7 (15th July 2017) - Kuwata, Kazuaki; Hanaya, Kengo; Sugai, Takeshi; Shoji, Mitsuru
Graphical abstract: Abstract: The chemo-enzymatic synthesis of ( R )-5-hydroxymethyl-2-isopropyl-5-methylcyclopent-1-en-1-yl trifluoromethylsulfonate, a potential chiral building block for polycyclic terpenoids containing a five–membered ring having isopropyl and angular methyl substituents, such as erinacin A and dolatriol, was achieved over 11 steps from ethyl 2-oxocyclopentane-1-carboxylate. The key synthetic precursor for this triflate was ethyl (1 S, 2 R )-2-hydroxycyclopentanecarboxylate (>99% ee), which was prepared by a lipase-catalyzed enantioselective hydrolysis of the corresponding racemic acetate. The antipodal ( S )-triflate is expected to be the synthetic intermediate for another group of terpenoids involving hamigeran B and stolonidiol. Enantiomerically pure (1 R, 2 S )-hydroxyester (>99% ee) was prepared in high yield using the asymmetric reduction of the oxoester with commercially available carbonyl reductase, "Chiralscreen® OH"-E001. Abstract : ( R )-5-Hydroxymethyl-2-isopropyl-5-methylcyclopent-1-en-1-yl trifluoromethylsulfonate: C11 H17 F3 O4 S ee >99% by HPLC of the starting material, ethyl (1 R, 2 S )-2-hydroxycyclopentanecarboxylate on Chiralcel OD-H [ α ]D 22  = +2.5 ( c 1.24, CHCl3 ) Source of chirality: lipase-catalyzed kinetic resolution and stereoselective methylation Abstract : Ethyl (1 S, 2 R )-2-hydroxy-1-methylcyclopentanecarboxylate: C9 H16 O3 ee >99% by HPLC of the starting material, ethyl (1 R, 2 S )-2-hydroxycyclopentanecarboxylate on Chiralcel OD-H [ α ]D 20  = −28.5 ( c 1.19, CHCl3 ) Source of chirality: lipase-catalyzed kinetic resolution and stereoselective methylation Abstract : Ethyl ( S )-2-methyl-2-oxocyclopentanecarboxylate: C9 H14 O3 ee >99% by HPLC of the starting material, ethyl (1 R, 2 S )-2-hydroxycyclopentanecarboxylate on Chiralcel OD-H [ α ]D 21  = +13.9 ( c 1.25, CHCl3 ) Source of chirality: lipase-catalyzed kinetic resolution and stereoselective methylation Abstract : Ethyl (2 S, 3 E )-3-ethylidene-2-methyl-2-oxocyclopentanecarboxylate: C11 H16 O3 ee >99% by HPLC of the starting material, ethyl (1 R, 2 S )-2-hydroxycyclopentanecarboxylate on Chiralcel OD-H [ α ]D 20  = +1.9 ( c 1.22, CHCl3 ) Source of chirality: lipase-catalyzed kinetic resolution and stereoselective methylation Abstract : Ethyl ( S )-3-isopropyl-1-methyl-2-oxocyclopentanecarboxylate: C12 H20 O3 ee >99% by HPLC of the starting material, ethyl (1 R, 2 S )-2-hydroxycyclopentanecarboxylate on Chiralcel OD-H [ α ]D 21  = +64.4 ( c 1.18, CHCl3 ) Source of chirality: lipase-catalyzed kinetic resolution and stereoselective methylation